Incorporating Climate Change Impacts and Adaptation in Environmental Impact Assessments Opportunities and Challenges - Agrawala, Shardul (OECD Publishing, 2011)
National governments and development agencies have invested considerable effort in recent years to develop methodologies and tools to screen their projects for the risks posed by climate change. However, these tools have largely been developed by the climate change community and their application within actual project settings remains quite limited. An alternate and complementary approach would be to examine the feasibility of incorporating consideration of climate change impacts and adaptation within existing modalities for project design, approval, and implementation. Environmental Impact Assessments (EIA) are particularly relevant in this context
Keywords: Environment